If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + h + h = 0 Combine like terms: h + h = 2h 2h + h = 0 Combine like terms: 2h + h = 3h 3h = 0 Solving 3h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '3'. h = 0 Simplifying h = 0
| 6y+2(y+3)=2 | | (x-3)(x+8)(x-5)=360 | | (6/11)*(6/11) | | 8+1.7x=9 | | 30k+100=2k+120 | | X-6(6-x)=4-x | | -4f+7=-5f | | 3/4x+2=7 | | 15=2x+75 | | 10(9+2n)= | | X+26+6=3x+6 | | d=2/3c | | 3/5k=2 | | -4/7*9 | | a=6(a+4) | | 4x+3x-10=11 | | 2(5f+9)= | | 3w^2-6w=24 | | (4/(3b-2))-(7/(3b+2)) | | (-7/11)*(2/5) | | 4x+8-7x=-22 | | 5+5b=5(1+5b) | | m=9+10m | | M/6-1=6 | | 7n-7=5n+7 | | 235=45X | | 7m-4=8m+5-m | | -8=6x+10 | | -6-3n=-6n | | 4x-33+3x+22=180 | | 4x-33+3x+22=180 | | 12-(6v+7)=-6v-5 |